2014
DOI: 10.5935/abc.20140003
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Parameters and Survival in Chagas Heart Disease with Severe Systolic Dysfunction

Abstract: BackgroundEchocardiography provides important information on the cardiac evaluation of patients with heart failure. The identification of echocardiographic parameters in severe Chagas heart disease would help implement treatment and assess prognosis. ObjectiveTo correlate echocardiographic parameters with the endpoint cardiovascular mortality in patients with ejection fraction < 35%. MethodsStudy with retrospective analysis of pre-specified echocardiographic parameters prospectively collected from 60 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 17 publications
1
14
0
3
Order By: Relevance
“…Consistent with the literature, we found the highest rates of mortality in patients in Stage D, the most severe stage of cardiomyopathy based on left ventricular dilatation and ejection fraction. Stage D T. cruzi infected individuals experienced 40% mortality over 14 months, similar to other studies of severe CCM (19). By restricting the analysis to patients in Stage D, we effectively examined the additive predictive value of the serum biomarkers beyond the clinical indicators already identified in many previous studies (10-12) (13) (14, 15) (9).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the literature, we found the highest rates of mortality in patients in Stage D, the most severe stage of cardiomyopathy based on left ventricular dilatation and ejection fraction. Stage D T. cruzi infected individuals experienced 40% mortality over 14 months, similar to other studies of severe CCM (19). By restricting the analysis to patients in Stage D, we effectively examined the additive predictive value of the serum biomarkers beyond the clinical indicators already identified in many previous studies (10-12) (13) (14, 15) (9).…”
Section: Discussionsupporting
confidence: 87%
“…Other less consistently identified risk factors include older age and male sex (11) (12) (14) (13) (16) (17). In recent retrospective study including only individuals with severe cardiomyopathy, low ejection fraction did not show further predictive value for mortality within this severely ill group (18) (19). …”
Section: Introductionmentioning
confidence: 92%
“…This study used the cut-off point of 72 mL/m 2 , similarly to that determined by Rassi et al, 19 who identified, by using the ROC curve, 70,71 mL/m 2 as the best cut-off point. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Of the 20 echocardiographic parameters studied, ILAV proved to be the only independent predictor of cardiovascular mortality in patients with Chagasic HF. 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…In patients with Chagas disease, most studies and clinicians have focused on the body structure and function components such as cardiac function 12 , 13 , myocardial dilation 14 , and functional capacity 10 . Despite the importance of the presence of depressive symptoms in Chagas disease and the impact of these symptoms on clinical management, few studies have investigated these symptoms.…”
Section: Introductionmentioning
confidence: 99%